On the job promoting Raton (Raton Range Raton, NM, 1984)
This article is about Janet Parr introducing herself to the city's leaders and merchants as the Chamber's new Executive Director.
Newspaper article + photograph of Janet Parr
Master list item #: 10
File location is in the Raton file Cabinet
Keywords: Parr, Janet -- Raton Chamber Executive Director; Raton Chamber of Commerce; Chamber Promotion; Local History; Life and Customs; Local Business; New Directors; Raton, New Mexico